2020
DOI: 10.1038/s41598-020-72332-9
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of patellar maltracking with 3 T dynamic magnetic resonance imaging: feasibility of a robust and reliable measuring technique

Abstract: Patellofemoral maltracking predisposes the patellofemoral joint to instability. The purpose of this study was to provide a reliable dynamic magnetic resonance imaging (MRI) measuring technique for patellofemoral maltracking, and to investigate the influence of anatomical risk factors (AF) on patellar maltracking. Ten patients (2 males,8 females, average 19 years) with clinical maltracking and 20 controls (10 males,10 females,average 28 years) were examined with a dynamic, multi-slice gradient-echo MRI sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
2
18
0
2
Order By: Relevance
“…A post hoc power analysis was conducted using G*Power software (version 3.1.9.6). It has been reported that the most valuable radiological parameters to detect the presence of patellar maltracking reliably were TT–TG distance and patellar tilt [ 20 ]. Thus, the mean values of these variables were used for the calculation.…”
Section: Resultsmentioning
confidence: 99%
“…A post hoc power analysis was conducted using G*Power software (version 3.1.9.6). It has been reported that the most valuable radiological parameters to detect the presence of patellar maltracking reliably were TT–TG distance and patellar tilt [ 20 ]. Thus, the mean values of these variables were used for the calculation.…”
Section: Resultsmentioning
confidence: 99%
“…The trochlear depth was assessed by measuring the distances between the posterior condyle line and the medial (MCD) and lateral condyles (LCD) as well as the lowest part of the trochlear groove (LTG). Trochlear depth was calculated according to the formula (MCD + LCD) / 2-LTG [ 18 ]. The morphological classification is based on the four types described by Dejour et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 Dynamic magnetic resonance imaging (MRI) has gained popularity in recent years with the advent of increasingly versatile imaging sequences and a growing list of potential clinical applications. The clinical utility of dynamic MRI in the musculoskeletal system is wide-ranging, from patellofemoral kinematics [1][2][3] to imaging of the hip in femoroacetabular impingement 4 and also dynamic spine imaging. 5,6 Especially when combined with thorough clinical evaluation, confirmation of abnormal joint kinematics by real-time MRI may be of considerable value in supporting therapeutic measures such as surgery or physical therapy.…”
Section: See Related Article On Page 1571mentioning
confidence: 99%